REVIEW ON IOT BASED THREATS, VULNERABILITIES & CHALLENGES OF INCIDENT RESPONSE USING EMBEDDED SYSTEM FOR SENSOR NODES - Vaishnavi Rajeshsingh Thakur; Dr. A. M. Rawate; Dr. Syeda Sumera Ali (International Journal of Innovations in Engineering Research and Technology, 2021)
The Internet of Things (IoT) is the technology innovation of the century and will forever impact how future generations communicate, work, and handle personal day-to-day tasks. IoT devices streamline processes and often automate everyday household tasks. Despite all the hype and added benefits to their uses, they continue to be the spotlight of recent breaches, privacy concerns, and security vulnerabilities and incidents. The purpose of this study is to shed light on the current threat landscape as it relates to the Internet of Things (IoT) while addressing the reasons why IoT devices are prime targets for attack.Additionally, the study examines the challenges of network defenders, incident responders, and forensic examiners face when investigating incidents.The study found IoT devices are plagued by many software and hardware vulnerabilities, most of which are examined and researched heavily by the Open Web Application Security Project (OWASP). Solutions include providing education to consumers on the risks and mitigations associated some of the more common vulnerabilities. Device manufacturers have a role to play in securing devices before they are released to the general market. Solutions to the challenges faced by Incident Responders and Computer Forensics examiners includes preparation before the incident or crime occurs. Proposed solutions include creating investigative and analytical procedures applying specifically to the Internet of Things. Including understanding their internal makeup, where data is stored, and to whom data is transferred. Answering each of these questions provides potential sources of evidence used to paint an overall picture of the root cause of incidents and events.